ایڈورڈ ولیم لین بطور مترجمِ قرآن کریم - پروفیسر ڈاکٹر محمد سلطان شاہ; ڈاکٹر حافظ خورشید احمد قادری (jihat-ul-islam, 2022)
Edward William Lane (1801-1876) was a British orientalist, translator and lexicographer. His timeless work An Arabic-English lexicon has been appreciated by all researchers working in the field of Arabic and Islamic Studies. Lane's stay in Egypt enabled him to learn Arabic directly from the native people. He adopted some habits of the Muslim community and mixed with them freely. He was very tolerant in his behavior and neither ridiculed Islam nor criticized it. Lane translated some extracts from the Qur'an and published them as a book. His introduction borrows information from the preliminary discourse of George Sale and Lane amended it in such a way that it became acceptable to Muslims. This article examines Lane's translation and compares it with Sale's rendering. It also discusses his Lexicon and translation of fragments of the Qur'an therein.